2017
DOI: 10.22401/jnus.20.4.08
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Additives on Denture Base Resin Properties

Abstract: Numerous studies have been carried out on studying the effect of glass fiber and ZrO 2 Nanoparticles alone on the mechanical properties of PMMA, to date, no investigations were made that have studied the mechanical properties of PMMA reinforced with glass fiber and zirconium oxide together as a hybrid composite.In this research the effect of addition of glass fibers (woven and chopped) and Zirconium oxide Nano-particles (ZrO 2 ) with different weight percent to the conventional poly (methyl methacrylate) (PMMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Our study demonstrated that the addition of different concentration of NaF improve the hardness of acrylic resin and there is a highly significant difference between treated groups when compared with the control group as shown in Tables (4, 5, and 6), which may be attributed to the increasing of crystals per unit area due to the elevation in NaF concentration in acrylic resins because the crystals of NaF may be harder than acrylic polymers thus, more resistance will be provided to indenter penetrations with more hardness values will be acquired, and this result is consistent with (7,9) . Nevertheless, the results in the current study revealed a highly significant difference in roughness value for most groups which is considered an undesirable property, that may be due to interference of NaF in the polymerization process.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study demonstrated that the addition of different concentration of NaF improve the hardness of acrylic resin and there is a highly significant difference between treated groups when compared with the control group as shown in Tables (4, 5, and 6), which may be attributed to the increasing of crystals per unit area due to the elevation in NaF concentration in acrylic resins because the crystals of NaF may be harder than acrylic polymers thus, more resistance will be provided to indenter penetrations with more hardness values will be acquired, and this result is consistent with (7,9) . Nevertheless, the results in the current study revealed a highly significant difference in roughness value for most groups which is considered an undesirable property, that may be due to interference of NaF in the polymerization process.…”
Section: Discussionsupporting
confidence: 75%
“…since it is the most increased fluoride compound release than other fluoride types followed by Caf 2 then amine fluorides. This can be associated with the compound's solubility, and its easily dissolving to free Na+ & F-ions (8,9) . Jasim BS & Ismail., 2014, Abdulsattar MH (2023) and Abdul-Latif Rashid A & Mousa Ouda L (10,11,12) used various sodium fluoride concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Dentures are prosthetic equipment is produced to substitute missing teeth, which is held by soft and hard tissues of the oral cavity. Dentures are made from many materials like (cellulose plastics, polyvinyl chloride [2]. In many instances the traditional denture remains the best treatment for medical and economic reasons, a perfect denture base material must include sufficient mechanical and physical features in addition to biocompatibility there is also aesthetics, polymethyl methacrylate (PMMA) is usually employed to make denture base material because of its multiple benefits which have (low price, biocompatibility, quite simple to process, stability in the oral atmosphere, and good appearance [3].…”
Section: Introductionmentioning
confidence: 99%
“…There are some ways to reinforce PMMA such as the addition of fibers. [7][8][9] Further improvements have been made with nanoparticles. [10][11][12][13][14] The flexural strength has a crucial role in acrylic resins resistance to forces which are induced in oral environment, so evaluation of flexural strength is considered as one of the most important characteristics of mechanical properties of acrylic resin.…”
Section: Introductionmentioning
confidence: 99%
“…There are some ways to reinforce PMMA such as the addition of fibers. 7 8 9 Further improvements have been made with nanoparticles. 10 11 12 13 14 …”
Section: Introductionmentioning
confidence: 99%